Cinobufagin induces acute promyelocytic leukaemia cell apoptosis and PML-RARA degradation in a caspase-dependent manner by inhibiting the β-catenin signalling pathway. (31st December 2022) - Bian, Yaoyao; Xue, Mei; Guo, Xinlong; Jiang, Wenjuan; Zhao, Ye; Zhang, Zhaofeng; Wang, Xian; Hu, Yongkang; Zhang, Qi; Dun, Wenliang; Zhang, Liang
Abstract: Context: Acute promyelocytic leukaemia (APL) is a malignant hematological tumour characterized by the presence of promyelocytic leukaemia–retinoic acid receptor A (PML-RARA) fusion protein. Cinobufagin (CBG) is one of the main effective components of toad venom with antitumor properties. However, only a few reports regarding the CBG treatment of APL are available. Objective: We explored the effect and mechanism of action of CBG on NB4 and NB4-R1 cells. Materials and methods: We evaluated the viability of NB4 and NB4-R1 cells treated with 0, 20, 40, and 60 nM CBG for 12, 24, and 48 h. After treatment with CBG for 24 h, Bcl-2 associated X (Bax), B-cell lymphoma 2 (Bcl-2), β-catenin, cyclin D1, and c-myc expression was detected using western blotting and real-time polymerase chain reaction. Caspase-3 and PML-RARA expression levels were detected using western blotting. Results: CBG inhibited the viability of NB4 and NB4-R1 cells. The IC50 values of NB4 and NB4-R1 cells treated with CBG for 24 h were 45.2 nM and 37.9 nM, respectively. CBG induced NB4 and NB4-R1 cell apoptosis and PML-RARA degradation in a caspase-dependent manner and inhibited the β-catenin signalling pathway. Discussion and conclusion: CBG induced NB4 and NB4-R1 cell apoptosis and PML-RARA degradation in a caspase-dependent manner by inhibiting the β-catenin signalling pathway. This study proposes a novel treatment strategy for patients with APL, particularly those with ATRA-resistant APL.